2020
DOI: 10.3889/oamjms.2020.4282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcome between Craniectomy and Craniotomy as Surgical Management of Traumatic Acute Subdural Hematoma: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Acute subdural hematoma (ASDH) is a major problem in traumatic brain injury. Surgical techniques for treating ASDH are varied, including cranioplastic craniotomy and large decompressive craniectomy. The superiority of craniectomy and craniotomy for treating ASDH is still controversial. AIM: The aim of this study was to compare the clinical outcome between craniectomy and craniotomy for treating traumatic ASDH through systematic review and meta-analysis. METHODS: This study used electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…18 In a meta-analysis conducted by Mahadewa, et al in 2020, comparing GCS score between craniectomy and craniotomy in patients with traumatic acute subdural hematoma, revealed craniectomy had poorer clinical outcomes with a pooled risk ratio of 1.41 (95% CI: 1.06-1.88; p=0.02). 19 The opposite conclusion was put forward by Leghani, et al in 2013. Research by Legnani, et al involving 152 patients demonstrated that performing a suboccipital craniotomy has similar effectivity and safety compared to performing a craniectomy.…”
Section: Discussionmentioning
confidence: 92%
“…18 In a meta-analysis conducted by Mahadewa, et al in 2020, comparing GCS score between craniectomy and craniotomy in patients with traumatic acute subdural hematoma, revealed craniectomy had poorer clinical outcomes with a pooled risk ratio of 1.41 (95% CI: 1.06-1.88; p=0.02). 19 The opposite conclusion was put forward by Leghani, et al in 2013. Research by Legnani, et al involving 152 patients demonstrated that performing a suboccipital craniotomy has similar effectivity and safety compared to performing a craniectomy.…”
Section: Discussionmentioning
confidence: 92%